The Impact of Cybergogy on Student Engagement and Autonomy in Digital Classrooms - Ibnu Fitiranto; Nurhuda Alfina Layalin (PT Mutiara Bustan Ilmu, 2026)
This study examines the impact of cybergogy on student engagement and autonomy in digital classrooms. Using a qualitative case study approach, the research explores how digital learning environments, supported by interactive technologies and multimedia tools, influence students’ participation and self-directed learning behaviors. Data were collected through interviews, observations, and documentation involving students and instructors engaged in online learning activities. The findings reveal that cybergogy significantly enhances student engagement by fostering active interaction, collaboration, and motivation. In addition, it promotes learner autonomy by encouraging students to manage their own learning processes, set goals, and monitor their progress. However, challenges such as limited technological infrastructure, unequal access to digital resources, and variations in students’ readiness for independent learning were also identified. The study concludes that effective implementation of cybergogy requires strong institutional support, teacher competence, and well-designed digital learning environments to maximize its benefits.